Dry Eye Syndrome in Glaucomatous Patients using Topical Anti-Glaucoma Therapy - Zulfiqar, Nabila; Ansari, Muhammad Sufyan Aneeq; Nafees, Khurram; Nawaz, Rabia; Shaheen, Manzra (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine the frequency of Dry eye in Glaucoma patients using topical anti-glaucoma therapy. Study Design: Descriptive Observational study. Place and Duration of Study: Study was conducted in outpatient department of Fatima Memorial Hospital Shadman, Lahore, from October 2016 to February 2017. Material & Methods: In this study, 61 diagnosed cases of glaucoma were included. Patients with significant dermatological problems that may be associated with dry eye such as rosacea and blepharitis were excluded from the study. The individuals were assessed by consultant Ophthalmologist for Dry eye syndrome having symptoms of stinging and burning sensations itching, watering, irritation, due to regular use of topical anti-glaucoma drugs. A written consent was taken from every patient before the test. The ocular surfaces of the patients were evaluated using Tear film break-up time test and Basal Schrimer’s test. Patients having TBUT less than 11 seconds were categorized as having dry eye. The degree of dryness was categorized as mild, moderate and sever Dry eye. Results: Among 61 patients of glaucoma using topical anti-glaucoma therapy, 22 (36.1%) were male and 39 (63.9%) were female. Mean age of the patients was 50.76 ± 15.67 years. On the basis of Tear film Break-up time test, 49 (81%) patients had Tear Break-up time less than 10 seconds and 12 (19%) patients were normal. On the basis of Schrimer`s test 51 (83.66%) patients had Dry eye. Conclusion: Topical use of anti-glaucoma therapy affects tear film stability and its functions leading to Dry eye syndrome.